DAMPAK FOMO TERHADAP KEGAGALAN INVESTASI MAHASISWA FAKULTAS EKONOMI DAN BISNIS ANGKATAN 2025 DI UNIVERSITAS UDAYANA - Laura Heliana BR Tarigan; Chellsy Mentelina BR Naibaho; Salman Sulthan Syamil; I Made Prema Arya Kusuma; Ni Kadek Intan Purnamasari; Pande Luh Sri Purwaningsih; Nathasya Tesalonica Anggraini Sibarani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
In recent years, interest in investing among young people, especially students, has increased significantly. The purpose of this study is to understand the impact of FOMO on investment failures among students of the Faculty of Economics and Business, class of 2025, at Udayana University. This study was conducted using a quantitative questionnaire method through a survey distributed to a sample group. The investment instruments used included stocks, mutual funds, and digital assets. However, the results of the study indicate that many students experience failure because they follow social media trends or FOMO. This phenomenon shows a lack of financial literacy, particularly in making investment decisions, which leads to a high risk of failure. The findings of this study emphasize the importance of financial literacy as a preventive measure to avoid failure due to FOMO in investing.